EFL Students’ Anxiety in Writing Scientific Papers for Publication: Levels and Types - Rahmawati, Olga Sintya; Hartono, Hartono; Nugroho, Kurniawan Yudhi (Journal of Advanced Multidisciplinary Research, 2024)
In recent years, some universities have required their students to publish scientific papers as one of the graduation requirements. These scientific papers can be in the form of articles published in scientific journals or in proceedings. Several factors affect the success of students in writing these scientific papers. One of them is writing anxiety. The study aims to investigate EFL students’ writing anxiety when writing scientific papers. The respondents were English Education and English Literature Study Program students (N=61). The data were collected with a questionnaire. The study found that the students have a moderate level of writing anxiety. The mean score of anxiety is 61.82, indicating a moderate level of writing anxiety. Somatic anxiety score ranged from 8.00 to 35.00, with a mean of 20.10 and a standard deviation of 5.29, while avoidance anxiety showed a mean of 17.80 with a standard deviation of 4.10. Cognitive anxiety scores ranged from 17.00 to 36.00, with a mean of 23.92. This was the highest mean score, followed by somatic anxiety, with avoidance being the least prevalent. The results of this study show that the majority of EFL students experience significant levels of anxiety when writing scientific papers for publications, and the three types of anxiety, namely cognitive anxiety, somatic anxiety, and avoidance behavior, play roles in the general level of writing anxiety. Implications of these findings suggest that educational institutions should provide academic support, particularly in helping students develop effective strategies to manage cognitive anxiety and improve topic selection processes, which could lead the students to enhance their writing performance and have a greater likelihood of successful publication.